Distribution dynamics in European venture capital - Michael Stolpe (Kiel Institute for World Economics (IfW), 2003)
This paper evaluates the evolution of European venture capital investments since 1990, using the distribution dynamics methodology. It tests and rejects the hypothesis that the international allocation of venture capital investments is driven by a pathdependent process of agglomeration, in which a country's initial advantage is transformed into a long-term lead. Instead, the evidence from a cross section of 13 European countries is more favourable for the alternative hypothesis, which explains international variations in venture capital investments as part of countries' different patterns of specialization. The robustness of these findings and implications for government policy are discussed.
Keywords: F21; G20; F43; 330; Distribution dynamics; Markov chains; New technology-based firms; Venture capital; Risikokapital; Investition; Unternehmensgründung; Regionale Konzentration; Internationale Arbeitsteilung; Schätzung; EU-Staaten